Penekanan Penyakit Blas pada Tanaman Padi melalui Perlakuan Cendawan Endofit Nigrospora sp. - Widodo, Widodo; Purnomo, Dyah Hariyanti; Giyanto; Wiyono, Suryo (Jurnal Fitopatologi Indonesia, 2022)
Suppression of Blast Disease in Rice Plants using Endophytic Fungus Nigrospora sp. Blast disease is one of the important diseases that can cause yield loss in rice plants. Disease control using resistant varieties and the use of fungicides is still not effective due to the high genetic variation of the blast pathogen, i.e.  the fungus Pyricularia oryzae. Biological control, including the use of endophytic fungi, is an alternative strategy to suppress this fungus. This study aimed to evaluate the application of soaking and spraying the endophytic fungus Nigrospora sp. in suppressing blast disease. The experiment was carried out in pots placed in an open field in the Bogor area from February to October 2021. The application of endophytic fungi included seed soaking, canopy spraying and a combination of both. As a treatment comparison was application of fungicide with the active ingredient tricyclazole and control treatment was plants that were not treated at all. Observations included disease incidence, disease severity and endophytic fungal colonization on leaf. Although the incidence of disease reached 100% for all treatments at the last observation periode (7 weeks after inoculation), the severity was suppressed by the treatment of Nigrospora sp. The endophytic fungus Nigrospora sp. was able to suppress the severity of leaf blast disease by 3.0%–25.3% and neck blast by 49.5%–61.6% when compared to controls. The most stable suppression of blast disease from the beginning to the end of the observation was shown by the combination treatment of seed soaking and spraying by Nigrospora sp. The ability of endophytic fungi to colonize rice plants ranged from 40.0%–55.6%.